IMPACT ON SOIL CHARACTERISTICS AND UNDER STORY VEGETATION OF CORIARIA NEPALENSIS IN NATURAL LANDSLIDE AREA - Bargali, Kiran; Joshi, Beena; Goel, Deepti (Ecoprint: An International Journal of Ecology, 2004)
Soil samples were collected from Coriaria canopy and ajacent open sites in natural landslide area in the central Himalaya. Herbaceous vegetation of each habitat were sampled in quadrats. The main soil attribute and species composition indicated significant differences in open and canopy habitats. Biomass was almost eight times higher in canopy habitat. Key words: Soil, Coriaria nepalensis, species composition, biomass. Ecoprint Vol.11(1) 2004.